Inappropriate Medication Use and Related Factors in the Elderly Living in Northern Iran - Afsaneh Dadashihaji; Atena Rahimi; Seyed Reza Hosseini; Ali Akbar Moghadamnia; Ali Bijani (University of Social Welfare & Rehabilitation Sciences, 2021)
Objectives: Older people are more prone to chronic diseases and are being treated than other age groups; as a result, they use more drugs that may be inappropriate and lead to adverse drug reactions. This study aimed to determine the rate of inappropriate drug use using the Beers criterion among the elderly in Amirkola City. Methods & Materials: The current descriptive-analytical study is part of the comprehensive plan "Study of the health status of the elderly in the Amirkola City" AHAP" (No.: 892917) which has been conducted as a Cohort study since 2011 on all people aged 60 and over in the Amirkola City, north of Iran. Necessary information was collected by a trained person using standard questionnaires that included the number, type and duration of drug use. The collected data were analyzed after entering the SPSS statistical software using Chi-square, Fisherchr('39')s Exact Test, and Logistic Regression to evaluate the status of inappropriate drug. P-value=0.05 was considered as a significant level. Results: The Mean±SD age of the elderly was 69.71±7.47 years. Prevalence of inappropriate drug use and drugs that should use by caution among the elderly was 37.58% and 29.85%, respectively. Glibenclamide (12.7%), Diclofenac (8.8%) and Clidinium C (5.4%) were among the most inappropriate drugs used in this population. The highest drug-drug interaction was related to the simultaneous use of two anticholinergic drugs. There was a statistically significant relationship between inappropriate drug use with gender, age, education level, employment status and marriage status (P<0.05). Conclusion: The rate of inappropriate drug use among the elderly in Amirkola is high compared to many other studies that expose the elderly to adverse drug reactions.